PERAN KLIEN DAN KOALISI DALAM IMPLEMENTASI KEBIJAKAN PENDIDIKAN INKLUSIF DI KABUPATEN BOGOR - Dary Amalia Fathin; Asep Sumaryana; Candradewini Candradewini (Universitas Padjadjaran, 2023)
This research is motivated by the policy of the Regulation of the Minister of National Education of the Republic of Indonesia No. 70 of 2009 whose implementation has not been optimal in Bogor Regency. It is known that the role played by the Cibinong SLBN as the source center has not run optimally. This study aims to examine more deeply the role or support provided by the Client (Target Group) and Coalition (Non-Government Actors) towards implementing inclusive education in Bogor Regency. This study uses the policy implementation model revealed by Najam (1995) regarding five critical factors that explain the success and failure of policy implementation. One of the critical factors expressed by Najam is the support of the Client and the Coalition. This research uses a descriptive qualitative approach. The informants in this study were 25 people, including 6 principals and 6 teachers at the six public elementary schools in Cibinong District, 6 parents of students with special needs, 6 school committees, and 1 head of the Cibinong SLBN Resource Center. Data collection techniques used are in-depth interviews and observation.The results showed that the support provided by the client was not optimal due to the busyness of the parents, the lack of understanding of the parents regarding the handling of children with special needs, as well as economic factors that made parents unable to take their children to doctors, therapists, or psychologists. The lack of socialization to all school members also causes the support that can be given to children with special needs and the implementation of inclusive education in schools is not yet optimal. Meanwhile, the support provided by the resource center has not been optimal due to problems in the number of human resources, distance, and time, as well as the lack of government support for the role played by SLBN Cibinong as a Resource Center. Penelitian ini dilatar belakangi oleh kebijakan Peraturan Menteri Pendidikan Nasional Republik Indonesia No. 70 Tahun 2009 yang implementasinya belum optimal di Kabupaten Bogor. Diketahui bahwa peran yang dijalankan oleh SLBN Cibinong selaku pusat sumber belum berjalan optimal. Penelitian ini bertujuan untuk mengkaji lebih dalam peran atau dukungan yang diberikan oleh Klien (Kelompok Sasaran) dan Koalisi (Aktor non Pemerintah) terhadap penyelenggaraan pendidikan inklusif di Kabupaten Bogor. Penelitian ini menggunakan model implementasi kebijakan yang diungkapkan oleh Najam (1995) mengenai lima faktor kritis yang menjelaskan keberhasilan dan kegagalan implementasi kebijakan. Salah satu faktor kritis yang diungkapkan oleh Najam ialah dukungan Klien dan Koalisi. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Informan dalam penelitian ini berjumlah 25 orang yang meliputi 6 Kepala Sekolah dan 6 Guru di keeanam SDN di Kecamatan Cibinong, 6 Orang Tua Murid ABK, 6 Komite Sekolah, serta 1 Kepala RC SLBN Cibinong. Teknik pengumpulan data yang digunakan ialah wawancara mendalam, dan observasi.Hasil penelitian menunjukan bahwa belum optimalnya dukungan yang diberikan oleh klien disebabkan karena faktor kesibukan yang dimiliki orang tua, kurangnya pemahaman orang tua terkait penanganan ABK, serta faktor ekonomi yang membuat orang tua tidak bisa membawa anaknya ke dokter, terapis, maupun psikolog. Kurangnya sosialisasi kepada seluruh warga sekolah juga menyebabkan belum optimalnya dukungan yang dapat diberikan kepada ABK maupun penyelenggaraan pendidikan inklusif di sekolah. Sementara itu, belum optimalnya dukungan yang diberikan oleh pusat sumber dikarenakan persoalan kuantitas SDM, jarak, dan, waktu, serta kurangnya dukungan pemerintah terhadap peran yang dijalankan SLBN Cibinong sebagai Pusat Sumber.